Effect of Female Education on Family Size, Contraceptive Awareness and its Practice (Medical Forum Monthly, 2024)
Objectives: To determine the association of female education with family size ,contraceptive methods awareness and its practiceStudy Design: Descriptive / Cross-sectional study.Place and Duration of Study: This study was carried out at Gyane and Obs Department, Fauji Foundation Hospital from 1st Oct, 2011 to 31 Oct, 2011.Patients and Methods: One forty nine married females having children were included in the study. Subjects were patients from Out Patient Department Of Gynaecology and employees of Fauji Foundation Hospital. Data was collected through a questionnaire by convenience sampling.Results: A total of 149 females were selected by convenience sampling. Thirty five (23%) females were un-educated and 114 (77%) were educated from 5th grade to FCPS .Average age at marriage was found to be 22 years. Most of females were house wives 80 (53%) while rest 69 (46%) were working ,cashing their capabilities in field of teaching, nursing, medicine and working as Aya. One hundred and two (89%)of educated females were having small families i.e 4 or less children while 11 of uneducated were small family size the difference is statistically significant (p value<.01).Ninety six (83%) educated females were aware of contraceptive methods as compared to 23 (65%) of uneducated females and the result was statistically significant (pvalue<.05).Regarding use of contraception no statistically significant difference was noted between two groups as 19 (54%) of uneducated were using contraceptive methods compared to 75(65%) of educated females. Condoms were the most commonly used method 26 (17%),followed by IUCD 17 (11%) natural method (8%) and bilateral tubal ligation (8%) while rest of females were using combination of contraceptive methods.Conclusion: Education of females has association with family size and awareness of contraception while use of contraceptive methods has no association with education and some other motivational factors play role in the use of contraceptive methods.